El bíos en la urbe. Vida, ciudad y subjetividades contemporáneas - López, Bily (2025)
In Foucault’s thought, the city is one of the main devices for the exercise of biopower. However, it’s worth to remember that neither the city, nor life, nor the exercises of power have been the same through the time. If we consider that what Foucault called life and city have their margins in the discourses produced in Europe between the seventeenth and nineteenth centuries, then, in order to understand our present, is completely necessary doing contemporaries studies to understand how both discourses have been interwoven in more recent times to enable new forms of power exercises. In this text we analyze a Lewis Mumford’s work —a key thinker for twentieth century urbanism— where biological metaphors show how new discourses about life are transmitted in the configuration of the idea of the city itself. Finally, we examine the emergence of new resilient subjectivities that, at the intersection of bios discourses in the city, emerge as exacerbated forms of homo œconomicus, who has as mandate on his own survival in the biopolitical context of the Anthropocene.